GAMBARAN KETERSEDIAAN PANGAN, KECUKUPAN ENERGI, DAN PROTEIN SERTA STATUS GIZI IBU HAMIL PASCAPENGUNGSIAN ERUPSI GUNUNG SINABUNG KABUPATEN KARO TAHUN 2014 - Silvina Sri Hartati Manurung; Evawany Yunita Aritonang; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Pregnant women is one of the vulnerable groups in nutritional problems because pregnancyterm need a large number of nutrients. Natural disaster can affect the household food availablesuch as the eruption of Sinabung which is cause the destruction of agricultural that give impact inthe collapse of population economy. This is affect the nutritional status of pregnant women whennatural disaster occurs to leave the refugee. The purpose of this research is to find out thehousehold food available, the number of energy and protein adequacy and the nutritional status ofpregnant women post Sinabung’s eruption. This is a descriptive research with cross sectionaldesign. The 33 samples of this research are the whole population in 2nd and 3rd trimester range.This research takes the household food availabel, the number of energy and protein adequacy, andnutritional status data were analyzed by univariate to get the frequency distributions. The researchshows that most of the nutritional status of pregnant women based on Upper Arm Circle did nothave a high risk in Energy Chronic Malnutrition (<23,5 cm) is about 90,9%. Pregnant women foodavailable shows 54,5% in non adequate category and the adequacy of protein in pregnant womenshows 66,7% in non adequate category. The household food available shows only 45,5%household in a good level of food available, and the rest shows the households food available areinsecure because the economy of people is unstable yet caused of agriculture is not giving the cropsyet. It is required for the increase of pregnant women awareness in health nutritional needed whichis increased in the term of pregnancy and the centred effort from government to make sure the foodavailable in population in case of natural disaster ( eruption) which is affect the collapse ofagricultural and economical.Keywords: food available, energy and protein adequacy, nutritional status, post evacuation